Eksplorasi Strategi Karyawan Gen Z dalam Mencapai Kesejahteraan Holistik di Tengah Lingkungan Kerja Hibrid - I Gede Putu Lanang Raditiya Perbawa; I Putu Dharmawan Pradhana; I Gusti Ngurah Oka Ariwangsa; Made Ratih Nurmalasari (Economic Reviews Journal, 2026)
This study aims to explore the strategies applied by Generation Z employees in achieving holistic well being within a hybrid work environment. Changes in work patterns that combine remote working and on site working provide flexibility, but also create new challenges related to work boundaries, psychological pressure, and work life balance. Generation Z, as a productive age group that grows up in the digital era, has adaptive characteristics but is vulnerable to work stress if it is not supported by appropriate self management strategies. This study uses a qualitative approach with a phenomenological method to understand the subjective experiences of Generation Z employees in dealing with the dynamics of hybrid work. Data were collected through in-depth interviews, observation, and documentation, and then analyzed thematically. The results of this study are expected to provide an understanding of the forms of personal strategies used by Generation Z employees to maintain balance in physical, mental, social, spiritual, and financial aspects, and to contribute to the development of human resource management studies that focus on employee well-being in the modern work era.